Whole-genome sequencing analysis of Y chromosome microdeletion: a case report. Issue 12 (December 2020) - Gao, Zhixiang; Yuan, Feng; Li, Qiaoqiao; Xia, Renlan; Fu, Kai; Xue, Boxin; Liu, Xiaolong
The mechanisms by which Y chromosome microdeletions cause infertility have been well described; however, the therapeutic targets remain a challenge. Here, we used whole-genome sequencing to explore the mechanism of Y chromosome deletion and potential therapeutic targets in a patient with infertility. There were no abnormalities in the patient's medical history. Routine semen analysis showed immotile sperm and only two motile spermatozoa were occasionally see after centrifugation, indicating that the direct cause of infertility was an abnormal sperm count and motility. A Y chromosome microdeletion test revealed partial deletion of the AZFc region, including AZFc1, AZFc2, AZFc3, and AZFc4 . Whole-genome sequencing showed that the patient had seven harmful mutations, with only one significant epigenetic mutation, SH3KBP1 . Gene Ontology analysis of these meaningful mutations indicated involvement of cAMP signaling pathways. The patient's wife became pregnant following in vitro fertilization, and no significant abnormalities were found during prenatal examination. This case suggests that Y chromosome microdeletion and gene mutation may affect the cAMP signaling pathway, leading to reduced sperm quality and male infertility.